Towards flexible personalized learning and the future educational system in the fourth industrial revolution in the wake of Covid-19. Issue 1 (1st January 2021) - Whalley, Brian; France, Derek; Park, Julian; Mauchline, Alice; Welsh, Katharine
ABSTRACT: The concept of the Fourth Industrial Revolution is related to a ubiquitously connected, pervasively proximate (UCaPP) world and its response to Covid-19. Pedagogies need to be aligned with institutional 'quality education' and changes in the nature of the undergraduate student intake to formulate a 'Future Educational System'. Considerations include students from 'non-traditional' sources adapting to existing university structures and how procedures might accommodate these students in addition to changes and disruptions resulting from Covid-19. Mobile devices allow Personal Learning Environments (PLEs) to be developed in accordance with individual students' needs. PLEs allow ubiquitous, flexible structures to develop educational quality. Policies should involve connectivist approaches and active learning via broad curriculum development and appreciate the importance of individual student needs and capabilities, socio-economic as well as academic. We stress the importance of broadening access to higher education, particularly for those who have been 'neglected' by current procedures.